Effects of rhythm control on left atrial structure remodeling in atrial fibrillation and heart failure with preserved ejection fraction - Bai, Lin; Sun, Yuxi; Si, Jiping; Ding, Zijie; Zhang, Xinxin; Zhang, Yanli; Xia, Yunlong; Liu, Ying (Frontiers in Cardiovascular Medicine, 2023)
Background: The benefits of rhythm control for atrial fibrillation (AF) in heart failure with preserved ejection fraction (HFpEF) have not been conclusively determined. We assessed the effects of rhythm control on left atrial (LA) structure remodeling and prognosis in patients with AF and HFpEF. Methods: This was a retrospective, real-world, observational study involving patients diagnosed with AF and HFpEF. The cohort was divided into rhythm-control and rate-control groups depending on their treatment strategies. The primary outcomes were all-cause mortality, rehospitalization for any cause, HF-related rehospitalization, and stroke. Differences in follow-up LA structure parameters were also analyzed. Results: Compared to the rate-control group, patients in the rhythm-control group had a lower risk of HF-related rehospitalization even after adjusting for potential confounders (adjusted HR 0.605, 95% CI 0.413-0.887, p=0.010). Moreover, rhythm-control therapy led to marked reductions in LA echocardiographic indicators and a higher proportion of LA reverse remodeling (LARR). Conclusions: Rhythm-control therapy reverses LA structure remodeling and is associated with improved clinical outcomes; therefore, it is an optimal treatment approach for AF in HFpEF patients.